A Bibliometric Review of Factors Causing Burn Out - Subarkah, Firman; Iskandar, Yusuf (Poltanesa, 2024)
Burnout has garnered significant attention across multiple scientific disciplines, particularly in health, management, and psychology. This bibliometric review aims to delve into the factors influencing burnout, while also highlighting emerging trends, influential authors, and potential avenues for future research. Utilizing systematic data collection and analysis through VOS Viewer software, this study uncovers key themes, research contributors, and interdisciplinary connections within the realm of burnout literature. The findings reveal a substantial body of research dedicated to burnout, with academia notably engaged in its exploration. However, a notable gap exists in the emphasis on causal factors. Predominant contributors to burnout identified include excessive workload, work-life imbalance, and inadequate social support systems. This underscores the pressing need for comprehensive interdisciplinary collaboration to formulate effective prevention and intervention strategies. The study advocates for the integration of disciplines such as psychology, human resource management, and health to address burnout holistically. By bridging these diverse fields, researchers, policymakers, and practitioners can develop more nuanced and effective approaches to tackle burnout's adverse effects in both workplace settings and broader contexts. In conclusion, this review offers valuable insights for stakeholders invested in mitigating burnout's detrimental impacts. By recognizing the multifaceted nature of burnout and fostering collaboration across disciplines, the groundwork is laid for more robust and sustainable solutions to combat this pervasive phenomenon.